Study of Hr Planning, Recruitment and Deployment: Challenges of Recruitment Policies, Hr Policies and Practices: Exploring the Impact of Microfinance on Recruitment and HR Policies (Journal of Advances and Scholarly Researches in Allied Education, 2011)
During the past one decade or so microfinancehas caught the fancy of development practitioners worldwide. In India,microfinance2 gained momentum in early and mid 1990’s with emergence of Basix,SHARE and SNF as major players in microfinance. Between 2000 and 2003, a numberof new players (primarily Spandana and SKS) with innovative business modelsemerged on the microfinance radar of India. Their spectacular returns andscaleable business model attracted the attention of commercial banks like ICICIBank, HDFC Bank and ABN AMRO Bank.